2022
DOI: 10.1186/s12913-022-08093-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of individuals benefiting from the kakaritsuke-yakuzaishi (family pharmacist) system in Japan: a retrospective cohort study using an employment-based health insurance claims database

Abstract: Background The kakaritsuke-yakuzaishi system (henceforth, the family pharmacist system) which provides more health services than those by general pharmaceutical practice, was implemented in Japan in April 2016. To distribute medical resources and medical care expenditures appropriately, identifying the possible major beneficiaries of this system is essential. By analyzing administrative claims data through this retrospective cohort study, we identified modifiers of the potential benefits of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The family pharmacist system aims to facilitate centralized and consistent pharmaceutical care and enable the delivery of more effective and comprehensive pharmaceutical services by developing patient–pharmacist contracts. Therefore, individuals often visit pharmacies near their home 23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The family pharmacist system aims to facilitate centralized and consistent pharmaceutical care and enable the delivery of more effective and comprehensive pharmaceutical services by developing patient–pharmacist contracts. Therefore, individuals often visit pharmacies near their home 23 …”
Section: Methodsmentioning
confidence: 99%
“…In Japan, the separation between prescribing and dispensing is facilitated by developing a system through which physicians receive higher fees for fulfilling prescriptions to community pharmacies, compared with the fees they receive for dispensing drugs themselves. 23 The family pharmacist system aims to facilitate centralized and consistent pharmaceutical care and enable the delivery of more effective and comprehensive pharmaceutical services by developing patient-pharmacist contracts. Therefore, individuals often visit pharmacies near their home.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the rapid development of digital technology means that workers need to continuously learn and update their skills to adapt to new work environments and requirements.In summary, digitization and online labor are significant features of new forms of employment in today's labor market, exerting important impacts on workers, businesses, and society. Governments, businesses, and society should actively respond to these changes by strengthening policy-making and training support, promoting the sustainable development of new forms of employment, and achieving stability in the labor market and sustainable development for individual workers [4].…”
Section: Digitization and Online Labor Of New Forms Of Employmentmentioning
confidence: 99%
“…However, little is known about the impact of KI on patients’ health behaviors. A study on Kakaritsuke-Yakuzaihi , the pharmacist version of KI, reported its beneficial effects were limited to a specific patient population [ 10 ]. Regarding KIs, one study reported that having a KI was positively associated with visiting large-scale hospitals [ 11 ]; however, it reflected the need for a practitioner referral for the initial hospital visit.…”
Section: Introductionmentioning
confidence: 99%